2022
DOI: 10.1111/anec.12944
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular septal pacing versus left bundle branch pacing in the treatment of atrioventricular block

Abstract: Right ventricular apical pacing (RVAP) is widely used in clinical practice due to its low pacing threshold and simple operation. However, experimental evidence revealed that long-term RVAP damages the function of the left ventricle, which results in increased hospitalization rate, mortality, and incidence of atrial fibrillation (Kiehl et al., 2016;Sohn et al., 2017). While there is still a debate concerning the best pacing site of the right ventricular septum (Kaye et al., 2015;Muto et al., 2018), His pacing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…According to the current study, the short-term effects of LBBP and LVSP on cardiac function seem to be less substantial in practice (4-6, 9, 10, 12, 13, 16). There was no consistent outcome in terms of paced QRS duration, although practically all investigations demonstrated that the stimulus artifact to LV activation time (LVAT) in lead V5 or V6 (Stim-LVAT) of LBBP was shorter than that of LVSP (Table 1 (16). While only one study found no significant difference in Stim-LVAT between LBBP and LVSP (73 ± 15 vs. 81 ± 13 ms, P = 0.138), this study proved that LBBP seems to result in a small, but significant, improvement in ventricular synchrony when compared to LVSP by calculating QRS area using electrocardiography and vectorcardiogram (5).…”
Section: Lbbp Vs Lvspmentioning
confidence: 99%
“…According to the current study, the short-term effects of LBBP and LVSP on cardiac function seem to be less substantial in practice (4-6, 9, 10, 12, 13, 16). There was no consistent outcome in terms of paced QRS duration, although practically all investigations demonstrated that the stimulus artifact to LV activation time (LVAT) in lead V5 or V6 (Stim-LVAT) of LBBP was shorter than that of LVSP (Table 1 (16). While only one study found no significant difference in Stim-LVAT between LBBP and LVSP (73 ± 15 vs. 81 ± 13 ms, P = 0.138), this study proved that LBBP seems to result in a small, but significant, improvement in ventricular synchrony when compared to LVSP by calculating QRS area using electrocardiography and vectorcardiogram (5).…”
Section: Lbbp Vs Lvspmentioning
confidence: 99%
“…2,3 In recent years, conduction system pacing (CSP), a technique directly activating His bundle or left bundle branch, has attracted attention as a novel technique. [4][5][6][7][8][9][10] His bundle pacing (HBP) has demonstrated its feasibility and clinical benefits compared with RAVP. 4,5 Despite these advantages, HBP has some limitations in terms of technical aspects (e.g., relatively lower procedural success rates and a high and unstable pacing threshold in 5% to 10% of patients).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that LBBP was superior to LVSP in enhancing pacing characteristics, such as LVAT and QRS duration. 8,9 LVSP was not part of the success criteria for LBBAP in initial studies, [10][11][12][13][14][15][16][17][18][19] while the latest consensus document has included LVSP for LBBAP. 7 Recent clinical studies have demonstrated that LBBAP led to better outcomes than RVAP 10,11 ; LBBAP boasted a higher success rate and a more consistent pacing capture threshold than HBP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations